What is new in the etiopathogenesis and treatment of dermatitis seborrhoica (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2005)
Seborrhoeic dermatitis is a chronic and recurrent inflammatory skin disorder, usually involving the scalp, intertriginous regions or areas with numerous sebaceous glands. Seborrhoeic dermatitis is one of the most resistant to therapy dermatological disorders, and therefore every patient needs to be treated individually. Despite the fact that the diagnosis is relatively uncomplicated, no single and radical cure for seborrhoeic dermatitis has been found yet. The study presents aetiology, clinical presentation and treatment of seborrhoeic dermatitis.